KI HAJAR DEWANTARA, MENGURANGI PENGARUH BARAT SECARA KULTURAL - Wiryokusumo, Iskandar (Jurnal Budaya Nusantara, 2014)
The entry of Western values, among others through culture, has been known recently. Culturalvalues are mostly among others enter through technology and consumer goods as product of technology.One attempt tobalancevaluesof the West, which would be cultural values, performed byKi Hajar Dewantara, a National Cultural Educator once was. In an attempt balancing the effortsmade on the basis of Javanese culture is more family-oriented, independence, a sense of moralhigh priority and live in harmony with nature. Many of the teachings of Java is developed throughslogans and statements originating and noble values normative religious. So Western culture, suchas individualistic, rationalistic, and intellectualism can be compensated fairly and naturally.Keywords: Western values, Javanese culture, cultural values.